Social Representation of Community Therapy in Patients of a Psychosocial Care Center in South Ceará - Oliveira, Sidney Medeiros de; Alexandre, Lucimara Araújo Campos; Rodrigues, Francisco de Carvalho; Rocha, Hidemburgo Gonçalves (Amadeus International Multidisciplinary Journal, 2017)
The decentralization of health care in Brazil, which occurred in the last years since the 1988 constitution, has promoted changes in the mental health care sector. Some proposals for reform in the sector, such as the deactivation of psychiatric hospitals, were implemented. In place of the old asylums, new centers of mental health care emerged, with coexistence in open centers and use of multidisciplinary therapy. Today, the Psychosocial Care Centers called CAPS are already part of the reality of several cities in the country. In Ceará, there were several CAPS in the capital and the interior. In this context of changes also appeared a new therapeutic modality the Community Therapy - TC, implemented by professor Adalberto Barreto, first developed in Fortaleza in Quatro Varas Community, initiating a different approach of attention to mental health. In it the participants help themselves in overcoming their problems, improving their self-esteem and facilitating their return to social life. Our research was carried out with users of the CAPS in South Ceará area, aiming to study the influence of Community Therapy on the treatment of patients. The research was of qualitative character through interviews with users of the CAPS, participants of the Community Therapy. Conclusion: Community Therapy was perceived as positive, a contribution to emotional health. Socialization (environment of meeting with friends, a place of dialogue, where people are willing to listen, moment of fraternization) and a Ressignification (solution of a problem, development, a mental path, attitudes of sad people are softened) of the needs of its users.